Magnetic memory effect in FePd nanoparticles prepared by sonoelectrochemistry - Van, Nguyen Thi Thanh; Trung, Truong Thanh; Phu, Nguyen Dang; Nam, Nguyen Hoang; Hai, Nguyen Hoang; Luong, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics, 2012)
Abstract: Magnetic memory effect was newly observed in hard magnetic FePd nanoparticles prepared by sonoelectrochemistry. The applied magnetic field was changed in defined protocols during the magnetic relaxation process and the magnetic memory effect occurs when the field changes are larger than the critical field change of around 25 Oe. This magnetic memory effect can be explained by the magnetic reversal processes in strong interaction systems. The width of the energy barrier distribution of these hard magnetic particles is related to the critical field change deduced from this study.